Surgical Intervention Improves Long‐Term Survival in Stage IV Thymic Epithelial Tumors: Insights From a SEER Database Analysis - Hao Fu; Hongchao Xiong; Zhen Liang; Yunjiu Gou (Thoracic Cancer)
ABSTRACT Objectives This research evaluates how surgical intervention affects survival rates in individuals with stage IV thymic epithelial tumors (TET) based on data from the SEER database, offering essential information for clinical decision making. Methods The SEER database (2004–2020) provided data on stage IV TET patients, classified into surgical and non‐surgical groups. Analytical techniques, including propensity score matching (PSM) and inverse probability treatment weighting (IPTW), were employed. The primary and secondary outcomes evaluated were cancer‐specific survival (CSS) and overall survival (OS), respectively. Results Of 634 patients (394 diagnosed with thymoma and 240 with thymic carcinoma), 335 underwent surgery, while 299 did not. In univariate analysis, those who had surgery demonstrated significantly improved CSS and OS, with 5‐year survival rates of 74.6% for CSS and 62.3% for OS, compared to 41.4% and 26.0%, respectively, in the non‐surgical group. Multivariate analysis identified surgery as an independent factor for better CSS and OS. After applying PSM with 194 patients in each group, surgery continued to be associated with significantly improved CSS (HR = 0.417, 95% CI: 0.297–0.587, p < 0.001) and OS (HR = 0.457, 95% CI: 0.350–0.596, p < 0.001). Inverse probability of treatment weighting (IPTW) analysis confirmed these findings, showing better CSS (HR = 0.361, 95% CI: 0.265–0.492, p < 0.001) and OS (HR = 0.423, 95% CI: 0.335–0.535, p < 0.001). Subgroup analyses underscored the survival benefit of surgery for patients with stage IV thymoma and thymic carcinoma, including those with lymph node or distant metastasis. Conclusions For stage IV thymic epithelial tumors, the inclusion of surgery in multimodal treatment can improve patient survival.